A parvicapsulid (Myxozoa) infecting Sprattus sprattus and Clupea harengus (Clupeidae) in the Northeast Atlantic uses Hydroides norvegicus (Serpulidae) as invertebrate host - Køie, Marianne; Karlsbakk, Egil; Einen, Ann-Cathrine Bårdsgjtere; Nylund, Are (Folia parasitologica, 2013)
A myxosporean producing actinospores of the tetractinomyxon type in Hydroides norvegicus Gunnerus (Serpulidae) in Denmark was identified as a member of the family Parvicapsulidae based on small-subunit ribosomal DNA (SSU rDNA) sequences. Myxosporean samples from various Danish and Norwegian marine fishes were examined with primers that detect the novel myxosporean. Sprattus sprattus (Linnaeus) and Clupea harengus Linnaeus (Teleostei, Clupeidae) were found to be infected. The sequences of this parvicapsulid from these hosts were consistently slightly different (0.8% divergence), but both these genotypes were found in H. norvegicus. Disporic trophozoites and minute spores of a novel myxosporean type were observed in the renal tubules of some of the hosts found infected through PCR. The spores appear most similar to those of species of Gadimyxa Køie, Karlsbakk et Nylund, 2007, but are much smaller. The actinospores of the tetractinomyxon type from H. norvegicus have been described previously. In GenBank, the SSU rDNA sequences of Parvicapsulidae gen. sp. show highest identity (82%) with Parvicapsula minibicornis Kent, Whitaker et Dawe, 1997 infecting salmonids (Oncorhynchus spp.) in fresh water in the western North America. A phylogenetic analysis places P. minibicornis and Parvicapsulidae gen. sp. in a sister clade to the other parvicapsulids (Parvicapsula spp. and Gadimyxa spp.).
Keywords: sladká voda; fylogeneze; ryby; spory; DNA, Ribosomal; ribozomální DNA; Norway; Polychaeta; Norsko; Molecular Sequence Data; Genotype; Fish Diseases; ledviny; Base Sequence; stadia vývoje; nemoci ryb; Animals; Fishes; Myxozoa; Life Cycle Stages; Sequence Analysis, DNA; zvířata; Fresh Water; polymerázová řetězová reakce; sekvence nukleotidů; Parasitic Diseases, Animal; Spores; parazitární nemoci u zvířat; hostitelská specificita; Polymerase Chain Reaction; Phylogeny; Dánsko; Host Specificity; sekvenční analýza DNA; genotyp; Denmark; Kidney; molekulární sekvence - údaje